2018
DOI: 10.1111/ped.13471
|View full text |Cite
|
Sign up to set email alerts
|

Integration of radiology and clinical score in pediatric appendicitis

Abstract: US or abdominal X-ray in children with possible appendicitis should be integrated with PAS to determine the next steps in management. In the case of discordance between the clinical findings and radiology, prolonged observation or further imaging are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Multiple clinical decision tools to aid in the diagnosis of pediatric appendicitis have been described. 41,42 They vary widely in their congruence to published criteria for rigor in clinical decision rules. 22,43 Two of the more well-studied scores include the PAS and Alvarado scores.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical decision tools to aid in the diagnosis of pediatric appendicitis have been described. 41,42 They vary widely in their congruence to published criteria for rigor in clinical decision rules. 22,43 Two of the more well-studied scores include the PAS and Alvarado scores.…”
Section: Discussionmentioning
confidence: 99%
“…23 Previous studies have shown favorable outcomes when selective imaging is used in patients with an intermediate risk of appendicitis. [24][25][26][27] In a prospective, observational cohort study conducted by Saucier et al at an academic pediatric ED, 119 (60%) of enrolled patients were found to be intermediate risk for appendicitis (PAS 4-7). After a period of observation in the ED, the treating physician would reassess the patient and determine the need for a RLQ US.…”
Section: Discussionmentioning
confidence: 99%
“…Appendicitis is the most common surgical abdominal emergency in the developed world and developing world (17)(18)(19)(20)(21). Although anatomic variations are less common, most of the surprises encountered during an appendectomy are usually due to the various positions of the appendix.…”
Section: Discussionmentioning
confidence: 99%